Millennial-scale vegetation changes in the north-eastern Russian Arctic during the Pliocene/Pleistocene transition (2.7-2.5 Ma) inferred from the pollen record of Lake El'gygytgyn - Andreev, Andrei A.; Tarasov, Pavel E.; Wennrich, Volker; Melles, Martin (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The sediment record of Lake El'gygytgyn (67 degrees 30'N, 172 degrees 05'E) spans the past 3.6 Ma and provides unique opportunities for qualitative and quantitative reconstructions of the regional paleoenvironmental history of the terrestrial Arctic. Millennial-scale pollen studies of the sediments that accumulated during the Late Pliocene and Early Pleistocene (ca. 2.7 to 2.5 Ma) demonstrate orbitally-driven vegetation and climate changes during this transitional interval. Pollen spectra show a significant vegetation shift at the Pliocene/Pleistocene boundary that is, however, delayed by a few thousand years compared to lacustrine response. About 2.70-2.68 Ma the vegetation at Lake El'gygytgyn, currently a tundra area was mostly dominated by larch forests with some shrub pine, shrub alder and dwarf birch in understory. During the marine isotope stages G3 and G1, ca. 2.665-2.647 and 2.625-2.617 Ma, some spruce trees grew in the local larch -pine forests, pointing to relatively warm climate conditions. At the beginning of the Pleistocene, around 2.588 Ma, a prominent climatic deterioration led to a change from larch-dominated forests to predominantly treeless steppe- and tundra-like habitats. Between ca. 2.56-2.53 Ma some climate amelioration is reflected by the higher presence of coniferous taxa (mostly pine and larch, but probably also spruce) in the area. After 2.53 Ma a relatively cold and dry climate became dominant again, leading to open steppe-like and shrubby environments followed by climate amelioration between ca. 2.510 and 2.495 Ma, when pollen assemblages show that larch forests with dwarf birch and shrub alder still grew in the lake's vicinity. Increased contents of green algae colonies (Botryococcus) remains and Zygnema cysts around 2.691-2.689, 2.679-2.677, 2.601-2.594, 2.564-2.545, and 2.532-2.510 Ma suggest a spread of shallow-water environments most likely due to a lake-level lowering. These events occurred simultaneously with dry climate conditions inferred from broad distribution of steppe ...